Association between dietary inflammatory index and inflammatory biomarkers with outcomes of in vitro fertilization treatment. Issue 1 (7th October 2020) - Diba‐Bagtash, Fatemeh; Shahnazi, Mahnaz; Ghasemzadeh, Alieh; Jahanjoo, Fatemeh; Dolatkhah, Neda; Farshbaf‐Khalili, Azizeh
Abstract: Aim: To investigate associations between dietary inflammatory index (DII), high‐sensitivity C‐reactive protein (hs‐CRP) and interleukin‐6 (IL‐6) with outcomes of in vitro fertilization treatment. Methods: This observational prospective study included 144 women undergoing fresh in vitro fertilization cycles who attended infertility center of Al‐Zahra Hospital in Tabriz, Iran. DII was computed based on dietary intake assessed using a 3‐day 24‐h food record diary. Outcomes of in vitro fertilization in this study were considered fertilization rate, embryo quality and positive pregnancy test. Inflammatory biomarkers were measured on the day of embryo transfer. Results: There was no statistically significant difference between pregnant and nonpregnant women in terms of infertility and demographic characteristics, quantity of retrieved and fertilized oocytes, fertilization rate and number of transferred embryos ( P > 0.05). The mean quality scores of resultant embryos ( P < 0.001) and transferred embryos ( P = 0.019) were significantly lower in the group of pregnant women, indicating the better quality among them. Median (percentile 25–75th) DII in the pregnant women was 1.8 (0.5–2.7) and in the nonpregnant women was 1.6 (0.3–2.6). DII was significantly related to hs‐CRP ( r = 0.198, P = 0.017) but not to IL‐6. There were no significant relationships between DII, serum hs‐CRP, IL‐6 and in vitro fertilization outcomes ( P > 0.05). Conclusion: These findings demonstrate that serum hs‐CRP and IL‐6 concentration and DII are not predictive markers of in vitro fertilization cycle outcomes in women undergoing in vitro fertilization.